Spatiotemporal relationship between air pollution and upper respiratory tract infection cases among children under five: a case study of Nakuru County, Kenya (2020–2022) - John Kapoi Kipterer; Alieu Sowe; Mark K. Boitt; Charles N. Mundia (Discover Public Health)
Abstract Air pollution poses a significant threat to respiratory health, particularly for children under five in low- and middle-income countries, including Kenya. Nakuru County, experiencing rapid urbanization and poor waste management, has seen a rise in respiratory illnesses such as Upper Respiratory Tract Infections (URTI). This study analyzed pollutant levels (CO, NO2, SO2, and AOD) using remote sensing data from 2020 to 2022 to investigate the correlation between air pollution and respiratory health. Data from health facilities were mapped in ArcGIS, and pollutant data was processed using Google Earth Engine. Statistical analyses, including Pearson and Spearman tests, assessed the relationship between pollutants and URTI cases. Spatial analysis revealed moderate CO concentrations and consistent AOD levels, with a peak in URTI cases between May 2021 and February 2022. However, no clear seasonal correlation was observed with NO2, and SO2 levels remained low. The correlation analysis showed weak positive relationships between pollutants and URTIs, with Pearson coefficients of 0.042 and 0.002, respectively. Linear regression indicated that mean NO2 had the most substantial impact on URTI cases, while SO2 also showed a significant positive effect. In contrast, CO and AOD had minimal influence. The study highlights the importance of focusing on NO2, SO2 and waste management in public health interventions to address air pollution-related respiratory illnesses. Additionally, it underscores the need for further research into indoor air pollution, especially in overcrowded informal settlements, where socioeconomic factors and poor ventilation exacerbate health risks. Promoting clean cooking fuels like ethanol and public health campaigns on ventilation are recommended to reduce indoor air pollution and improve respiratory health in these vulnerable communities.